Linear Consecutive 3/7:F Repairable System with Priority in Repair - Nurwidiyanto Nurwidiyanto (Proceeding Of The International Seminar and Conference on Global Issues, 2015)
A Linear consecutive 3-out-of-7:F repairable system with one repairman is studied in this paper. When there are more than one failed component, priorities are assigned to the failed components.Assuming that system has only one repairman, both the working time and the repair time of a component are exponentially distributed. The rapirman assigned different priorities to the failed components. Through the analysis of the system and get some important reliability index of the system by using the general markov process and the tool of the Laplace transformation.